2010
DOI: 10.1128/jcm.02541-09
|View full text |Cite
|
Sign up to set email alerts
|

Use of Luminescent Leptospira interrogans for Enumeration in Biological Assays

Abstract: Rapid and reliable in vitro methods for the detection of pathogenic leptospires, such as Leptospira interrogans, are lacking. The present study investigated the use of luminescence to replace the existing enumeration techniques. Transposon TnSC189 was modified to incorporate the luxCDABE cassette from Photorhabdus luminescens and was used to construct luminescent Leptospira spp. There was a linear relationship between luminescence and cell number, with the theoretical detection limit being less than 10 4 lepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In a recent study, the luxCDABE cassette from Photorhabdus luminescens was transferred into Leptospira spp. to generate luminescent bacteria (26). In this work, we constructed a set of plasmid vectors which contain either gfp or mRFP1 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the luxCDABE cassette from Photorhabdus luminescens was transferred into Leptospira spp. to generate luminescent bacteria (26). In this work, we constructed a set of plasmid vectors which contain either gfp or mRFP1 alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Two key defenses against pathogens are macrophages and serum complement. L. interrogans is resistant to killing by serum complement (39,59), whereas the saprophytic species L. biflexa is sensitive. To assess whether the disruption of htpG in M1233 affected resistance to human complement, wildtype and M1233 cells were incubated with 90% pooled normal human serum at 37°C for 60 min; the viability of the cells was then determined by direct microscopic counts.…”
Section: Resultsmentioning
confidence: 99%
“…Nonmotile cells are considered nonviable (60), with direct microscopic counts employed as a measure of viability in several studies (9,59,61,62), including assessment of sensitivity to complement (59,61). Additionally, studies with luminescent leptospires have shown motility to be an accurate measure of cell viability (39). Leptospires tend to aggregate in culture and have diffuse colony morphologies (60) that make viable plate counts problematic and highly inaccurate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modifi ed transposons have been used, including those carrying different selection markers [ 5 , 17 ], an alternative origin of replication to allow purification of higher plasmid quantities [ 18 ], or addition of markers such as green fl uorescent protein [ 19 ] and the Photorhabdus luminescens luxCDABE luminescence genes [ 20 ]. Transposon insertions are stable, as the transposase is encoded outside of the transposon; mutants have retained the transposon during passage through animals, and over 100 generations in the absence of selection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%